CHALLENGES OF THE RECENT FINANCIAL CRISIS UPON THE EUROPEAN UNION ECONOMIC GOVERNANCE - MIHUȚ IOANA-SORINA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2015)
The process of economic governance constitute a property or a characteristic for a multitude of areas including markets, communities, societies, state, being considered a triggering factor at regional, national or supranational level. The European Union economic governance incorporates some key features, namely in this case the decisions are made as a result of an interconnected action between a complex network that implies different levels of governing. The purpose of this article is to investigate the obstacles that the process of EU economic governance had to overcome during the recent financial crisis and the measures that the responsible authorities adopted in order to improve the general efficiency of this system. The main conclusion of this article is that the recent financial crisis highlight the limits that the European Union economic governance had in implementing economic policies that assure a smooth path towards sustainable growth and convergence in the context of a continuous process of integration between the member states. The new model of economic governance concentrates upon a mechanism of monitoring and early reporting of any macroeconomic imbalances as well as an intensified monitoring activity within the budgetary field.